Efektivitas Alat Peraga Medan Magnetik Digital Berbasis Arduino Uno untuk Meningkatkan Pemahaman Siswa SMA - Sumiati, Sumiati; Ramadani, Santri; Fauzan, Alvin Syahrul; Rusdiana, Dadi (Gravity : Jurnal Ilmiah Penelitian dan Pembelajaran Fisika, 2024)
The study addresses the challenges often associated with the abstract nature and mathematical complexity of physics, particularly in relation to the concept of magnetic fields. To facilitate visual learning, the study aims to assess the efficacy of a teaching aid centered around a toroid, the researcher developed using Arduino Uno and Hall effect sensors. The research employs a quantitative one-group pretest-posttest design, measuring outcomes through test scores and student questionnaires. The N-Gain test indicates a moderate increase in student understanding concept. The results of the analysis of student responses through questionnaires had shown that students had found it easier to understand the magnetic field material when using Arduino-based magnetic field teaching aids, and the learning media used had made it easier for students to remember the magnetic field material. The findings support the effectiveness of the Arduino Uno-based digital magnetic field teaching aid in improving students' understanding of toroidal magnetic fields.